2018
DOI: 10.1017/s0021932017000682
|View full text |Cite
|
Sign up to set email alerts
|

Age at Menarche and Sexual Debut Among Young Filipino Women

Abstract: There has been a secular decline in age at menarche since the 19th century. Early-maturing women are more likely to have their sexual debut at a younger age, which in turn gives rise to a host of reproductive health and social problems. This study used data from five waves of National Demographic and Health Surveys conducted in the Philippines between 1993 and 2013 to examine the trends and socioeconomic differentials in age at menarche and sexual debut. The changing trend in age at menarche and sexual debut w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
3
1
0
Order By: Relevance
“…This is supported by an earlier report in South Africa where poor individuals, due to a lack of alternatives to livelihoods, end up engaging in sexual transactions (Ajah et al, 2015) d. Sexual Desire Research conducted by (Glynn et al, 2010) states that the age of sexual desire and age at marriage will increase with age at menarche. For example, among people with early menarche (<14 years of age, 60% were married and only 11% were not sexually active by 17 years of age, compared with 11% who were married and 71% were not sexually active among those with late menarche (ages ≥ 16) This is in line with research by (Tey et al, 2019) which states that sexual debut at the age of 15 in women who have their first menstruation before the age of 12 years is 4.4 times greater than those who have menstruation at the age of 14 years.…”
Section: Economy Conditionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is supported by an earlier report in South Africa where poor individuals, due to a lack of alternatives to livelihoods, end up engaging in sexual transactions (Ajah et al, 2015) d. Sexual Desire Research conducted by (Glynn et al, 2010) states that the age of sexual desire and age at marriage will increase with age at menarche. For example, among people with early menarche (<14 years of age, 60% were married and only 11% were not sexually active by 17 years of age, compared with 11% who were married and 71% were not sexually active among those with late menarche (ages ≥ 16) This is in line with research by (Tey et al, 2019) which states that sexual debut at the age of 15 in women who have their first menstruation before the age of 12 years is 4.4 times greater than those who have menstruation at the age of 14 years.…”
Section: Economy Conditionsupporting
confidence: 87%
“…This study was supported by (Tey et al, 2019) who found that only 7.2% of those aged 16-20 years are currently using the contraceptive method 29.6% (13.8% using pills and 1.5 % use condoms). The low contraceptive prevalence in the Philippines is partly due to religious opposition preventing the implementation of stronger programs to promote the use of modern contraceptives.…”
Section: Sexual and Reproductive Health Problemssupporting
confidence: 62%
See 1 more Smart Citation
“…Increasing age at marriage without a corresponding increase in access to reproductive health services for the unmarried means that more and more young women are exposed to the risk of out-of-wedlock/unplanned pregnancies, unsafe abortion, and STIs, including HIV (Baumgartner et al, 2010;Downing and Bellis, 2009;Glynn et al, 2010;Tey et al, 2019;Whatley et al, 1989). The Malaysian family planning programme does not provide contraceptive services to the unmarried, and this may have caused a rise in unplanned pregnancies and unsafe abortion among an increasing number of unmarried but sexually active young people.…”
Section: Discussionmentioning
confidence: 99%